Modelling the relationship between canopy projection area and above-ground carbon stock of intermingled canopy trees using high-resolution satellite imagery - Shah, S. K.; Acharya, H. (Banko Janakari, 2016)
This study was aimed to establish regression models for the relationship of Canopy Projection Area (CPA) with carbon stock of intermingled canopy trees of dominant species for the prediction of above-ground carbon stock. Manual delineation of CPA of intermingled canopy trees of the dominant species was carried out using GeoEye Satellite Image. Diameter at breast height of trees were measured in 56 sample plots. The above-ground dry biomass of trees was calculated from the field measured DBHs using allometric equation while the above-ground carbon stock of the trees were obtained by multiplying their dry biomass with the factor 0.47. Individual basal area of intermingled canopy trees was calculated separately and was summed up (ΣBA) along with the summation of their carbon stock (Σcarbon). Correlation analysis was carried out to assess the linear relationship between CPA, DBH, BA, biomass, and carbon stock. Four types of functions, viz., simple linear, quadratic, logarithmic and power were used to fit the data using least square regression method. Shorea robusta, Schima wallichii and Terminalia alata were found dominant tree species in the study area. The relationship of CPA with ΣBA and Σcarbon of intermingled canopy trees of Shorea robusta was found to be linear with R2 of 0.29 and 0.25 respectively. Simple linear regression model resulted in the least error for the prediction of carbon stock of intermingled canopy trees. The identified simple linear regression models having the least error are not applicable for the prediction of above-ground tree carbon stock of broadleaf forest in hilly terrain. Banko Janakari, Vol. 23, No. 2